Discovery of insertion-deletion polymorphism for identification on catfish species (Pangasianodon gigas, Pangasianodon hypophthalmus) - Kriangsak Mengumphan (2018)
© 2016, Chiang Mai University. All rights reserved. The mekong giant catfish (Pangasianodon gigas) and striped catfish (Pangasianodon hypophthalmus) are important fresh water catfish for aquaculture in Thailand. The two species are difficult to distinguish by morphological characteristics, especially in the larvae state. Thus, the aim of this study was to develop DNA markers for identifying these species. Ten potential of amplified fragment length polymorphism (AFLP) were sequenced and six sequence characterized amplified region (SCAR) markers were developed. However, only three markers (Pg1, Pg2 and Hf1) were clear PCR banding in 50 P. gigas, 50 P. hypophthalmus from six locations (10 samples/species/location) and 130 hybrid catfish (P. gigas×P. hypophthalmus). The nucleotide showed insertion and deletion (Ins/Del) polymorphism. The variation of these markers showed with 89.8% of concordant and 89.49% of the accuracy test to clearly separated P. gigas from another catfish species. Similarly, P. hypophthalmus showed 86.0% of concordant and 84.56% with the accuracy test. Whereas, in the 119 hybrid catfish were showed low concordant and accuracy test as 55.0% and 48.40%, respectively. These results indicated that the three markers have high potential to separate P. gigas and P. hypophthalmus species. However, additional markers are needed to ensure 100% accuracy for identify parental species and hybrids.